Network pharmacological analysis of Xuefu Zhuyu decoction in the treatment of atherosclerosis - Yuan, Jinxia; Yan, Fei; Li, Wei; Yuan, Guoliang (Frontiers in Pharmacology, 2022)
Objective: Using a network pharmacological approach, this study will evaluate the effect of Xuefu Zhuyu Decoction in the treatment of atherosclerosis. Methods: Import the data into the STRING database to construct a protein-protein interaction (PPI) network, and the network topology was analysed with the Bisogenet plug-in by Cytoscape 3.7.2. Using the R language Bioconductor platform, gene Ontology (GO) enrichment analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis for potential targets of Xuefu Zhuyu Decoction in the treatment of atherosclerosis, and import the results into Cytoscape 3.7.2. To map the results and create a KEGG network diagram, we used Cytoscape 3.7.2 for analysis. Results: A total of 91 chemical components and 1320 disease targets were obtained, including 138 cross-targets. TNF, AKT1 and ALB were identified as important targets, and GO functional analysis indicated that BP was the primary cause of oxidative stress. The primary action of MF is binding. KEGG has explored and enriched 149 signalling pathways, including the AGE-RAGE signalling system and the TNF signalling network. According to a study involving molecular docking, quercetin and β-carotene have a strong binding affinity for AKT1 and ALB. Conclusions: The potential of Xuefu Zhuyu Decoction to treat atherosclerosis through multiple components and targets provides a way to further study its mechanism.